Comparison of Graft Outcomes Reusing Original Intermediate-Term Cold Storage Solution for Entire Corneal Donor Storage Period With Exchanged Fresh Storage Solution After Donor Preparation in the Cornea Preservation Time Study. Issue 12 (9th December 2022) - Lass, Jonathan H.; Bailey, Ryan J.; Szczotka-Flynn, Loretta B.; Benetz, Beth Ann; Soper, Mark; Titus, Michael S.; Kollman, Craig; Beck, Roy W.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to evaluate outcomes of Descemet stripping automated endothelial keratoplasty comparing exchange with fresh intermediate-term cold storage solution after lenticule preparation versus reuse of the original solution in the Cornea Preservation Time Study. Methods: In the Cornea Preservation Time Study, 508 donor corneas had lenticules prepared by the eye bank with fresh solution exchange (Fresh group) and 283 with reuse of the original solution (Original group). Storage time for all donors was ≤11 days. Graft success rates, central endothelial cell loss at 3 years, and frequency of positive donor rim cultures were compared between the 2 groups. Results: The 3-year graft success rate (95% confidence interval) was 93.4% (90.7%–95.3%) in the Fresh group and 95.2% (91.8%–97.2%) in the Original group (adjusted hazard ratio for graft failure = 0.64, 95% confidence interval, 0.33–1.24, P = 0.19). The mean percentage endothelial cell loss was significantly greater in the Fresh group versus Original group (45% ± 22% vs. 38% ± 20%, respectively, P = 0.004). Cultures were positive in 4 (1.5%) of 267 donor rims (3 fungal and 1 bacterial) in the Fresh group and in 4 (2.5%) of 158 in the Original group ( P = 0.57). There were 2 postoperative infections in the Original group and none in the Fresh group. Conclusions: The use of the original intermediate-term cold storage solution did not reduce the 3-year graft success rate compared with exchanging with fresh solution after lenticule preparation for Descemet stripping automated endothelial keratoplasty, while the frequency of positive donor rim cultures did not significantly differ between groups.